Nationalism Education: Dialectical Relations Between Darussalam Islamic Boarding School Education and Tradition of the Manokwari Society of West Papua - Syarifah, Ma’isyatusy; Indriyani, Dian; Almachim, Ainul Churria (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2023)
Research refutes the opinion of Francis Fukuyama, in his book The End of History and the Last Man (2006) which states that nationalism is dead and does not need to be taught. This thesis was written to strengthen previous research which also questioned the existence of nationalism in the world of education such as Coulby and Zambeta (2007) which stated that the old ideology of nationalism which in certain aspects was universalistic, humanistic conceptualized by intellectuals, lost